Family Empowerment Model Based On Socio-Cultural Wisdom For Stunting Prevention In North Gorontalo Regency - Nasaru, Jumriyanti; Azam, Mahalul; Woro Kh, Oktavia; Yuniastuti, Ari (Health Science UDINUS, 2025)
Stunting prevalence affects 149.2 million children worldwide, compromising cognitive development and economic productivity. North Gorontalo Regency experienced an increase in prevalence from 23.6% to 30.5% between 2022 and 2023, highlighting the limitations of conventional interventions. This quasi-experimental study evaluated culturally integrated health promotion models through family empowerment among 384 households with children aged 0-59 months in North Gorontalo Regency. The study employed intervention groups (n=192) and control groups (n=192) using statistical and thematic analytical approaches. Interventions integrated Nola Pender's Health Promotion Model with indigenous Gorontalo socio-cultural wisdom through two-month participatory education programs and enhanced interpersonal communication strategies. Findings revealed substantial behavioral transformations: family knowledge scores improved by 34.2% (p<0.001), positive attitudes toward traditional feeding practices increased by 28.7% (p<0.01), and optimal childcare practice adoption rose by 42.1% (p<0.001) compared to control groups. The culturally adapted model effectively leveraged indigenous childcare wisdom and community social frameworks, achieving sustainable behavioral changes that integrate traditional practices with evidence-based stunting prevention approaches, thereby enhancing program acceptance and effectiveness.